Effects of sewage sludge on bio-accumulation of heavy metals in tomato seedlings - Elloumi, Nada; Belhaj, Dalel; Jerbi, Boutheina; Zouari, Mohamed; Kallel, Monem (Spanish Journal of Agricultural Research, 2016)
The proposal to use sewage sludge (SS) on agricultural fields as a sustainable way to dispose of the waste is based on its high organic and nutrients content. However, the presence of heavy metals (HMs) in sludge can contaminate crops and accumulate in the food chain. The aim of this study was to assess changes in soil fertility, biochemical responses of tomato (Solanum lycopersicum L. cv. Rio Grande) seedlings and the availability of HMs with increased rate application of SS (0, 2.5, 5 and 7.5%). Leaf chlorophyll content, nutritional status, proline, membrane peroxidation, stomatal conductance and HM accumulation were investigated. Results showed that the soil pH decreased, whereas soil salinity, organic carbon, total N, available P and exchangeable Na, Ca, K and HM content increased significantly with increasing application rates of SS. Among the three HMs (Zn, Cu and Cr), Zn had the highest capacity for transferring from soil into plants. Low metal translocation was observed from roots to leaves. The 7.5% SS dose decreased biomass production and caused a decline in chlorophyll content and stomatal conductance. However, lipid peroxidation and proline contents increased. Therefore, the use of 2.5 and 5% doses of sewage sludge in agriculture would be an efficient and cost-effective method to restore the fertility of soil and an environment-friendly solution for disposal problems.